Карнавал у Тель-Авіві: Пурим у першому івритомовному місті - Ар’є-Сапір, Н. (Народна творчість та етнографія, 2008)
The founders of Tel Aviv dreamed of a city whose character would be both Zionist and European. The annual of Purim carnivals in Tel Aviv held from 1909-1936 were a perfect reflection of the city's dual character. This paper socuses on the Purim processions and their key symbols which were the main feature of the carnival of Purim in Tel Aviv. These processions were dedicated to three main subjects: The Zionist enterprise, satirical performances related to actual political problems of the day and Purim's traditional themes, all performed in the spirit of the carnival. It follows that Purim in Tel Aviv was an appropriate means to display in public the most urgent needs of the renewing Jewish population in Eretz Israel during those years, namely the wish to express themselves freely and publicly, to have a national identity, to open themselves to the modern world and, at the same time, to remain attached to their roots.